The effect of evaluation of dry weight using bioimpedance method on residual renal function in maintenance hemodialysis patients - YANG Fan; LIU Xiao-jing; JIN Li-qin; YUAN Dan; JIAO Jian; CAO Qian-ying; LI Zhong-xin (Linchuang shenzangbing zazhi)
Objective To evaluate the dry weight of maintenance hemodialysis(MHD) patients using bioimpedance method and to observe the protective effect of the accurate evaluation of dry weight on residual renal function in patients with MHD. Methods Forty patients with MHD were enrolled, whose 24-hour urinary volumes were ≥400 mL. They were randomly divided into the trial group and control group. The dry weight in the trial group was determined with a bioimpedance analyzer, and the dry weight in the control group was evaluated clinically. After 4 months of follow-up, the 24-hour urine volume, body weight, mean arterial pressure, dialysis ultrafiltration volume, percentage of weight gain during inter-dialysis, BNP, EF value of colorful ECG, left ventricular mass index, and dialysis-related acute complications were compared between theirbaselines and values at the last follow-up. Results Thetrial group had lower mean arterial pressure \[(92.0±9.3) vs(96.5±8.5), P<0.05\], lower BNP \[(280.3±410.5) vs(471.7±786.0), P<0.05\], and higher 24-hour urine volume \[(649.2±289.3) vs(562.5±224.8),P<0.05\] than the control group. Conclusions The application of bioimpedance technology in accurately assessing dry weight can delay the urine reduction caused by excessive ultrafiltration,has a protective effect on residual renal function, and can improve mean arterial pressure at the same time. Increasing the frequency of detection may further reduce dialysis-related complications.